Tetrad Effect of Rare Earth Element Fractionation in Zircon from the Pegmatite of the Adui Massif, Middle Urals - Ekaterina V. Levashova; Sergey G. Skublov; Dmitry A. Zamyatin; Qiuli Li; Dmitry S. Levashov; Xianhua Li (Geosciences, 2023)
The zircon from the pegmatite of the Adui granitic massif displays the unique the rare earth element (REE) distribution spectrum with the tetrad effect in REE fractionation. The tetrad effect often occurs in granitoid rocks, but it is rarely encountered in minerals, e.g., zircon. Fluid saturated with volatiles, water and trace elements is a factor responsible for the tetrad effect in the zircon. The detailed isotopic-geochemical study of the zircon has revealed several zones differing in internal structure (in the back-scattered electron (BSE) image), composition and REE distribution. The zones indicate changes in the crystallization environment provoked by the evolution of the pegmatite-forming melt. They occur as the gradually growing changes in composition from the unaltered zones that are light-colored in BSE to the altered zones that are dark-colored in BSE. The unaltered zones are consistent in composition and geochemical features with magmatic zircons. The high content of trace (U, Th, REE) and volatile elements (F, Cl) in water suggests its crystallization from the fluid-saturated magmatic melt. The altered zircon zones occur as recrystallized zones with high content of non-formula elements (Y, Ca, Sr, Nb, P), a non-differentiated REE distribution spectrum and an absent Ce anomaly. These features are consistent with those of hydrothermal-metasomatic zircon.